Pemanfaatan Kecerdasan Buatan Dalam Era Digitalisasi Untuk Mendukung Kompetensi Siswa - Mona, Prahasti; Kalsum, Toibah Umi; Sallaby, Achmad Fikri; Asyhari, Ahmad; Dewantara, Dewantara (Universitas Dehasen Bengkulu, 2024)
Increasing the competency of Vocational High School students must continue to be improved through various strategies as an effort to prepare themselves to be able to compete in the world of work and industry. The aim of implementing this Community Service is to introduce the development of information technology through artificial intelligence in the era of digitalization in an effort to support student competence. The use of artificial intelligence through activities to introduce various artificial intelligence software or technologies is carried out through face-to-face methods which are carried out at SMKN 3 Bengkulu City. The strategy in community service activities is implemented through presentations and presentations involving resource persons by lecturers with assistance provided by students. Furthermore, in addition to presenting the material in the form of a presentation, an interactive dialogue was held with the participants regarding the material presented. Based on the results of implementing Community Service (PKM) activities, it can be concluded that students understand the use of artificial intelligence in supporting student competencies. Furthermore, during the implementation there was interactive interaction through questions from students regarding the development of artificial intelligence technology. This also shows that artificial intelligence in the digitalization era can support the competence of vocational high school students.